PENGARUH KEPEMIMPINAN HERMAN ABDULLAH SEBAGAI WALIKOTA KOTA PEKANBARU PERIODE 2001-2011 TERHADAP PEROLEHAN SUARANYA PADA PEMILIHAN GUBERNUR RIAU PUTARAN PERTAMA DI KOTA PEKANBARU TAHUN 2013 - Dewi, Chintamy Herma; ", Ishak (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This study aimed to explain the effect of Herman Abdullah leadership as Mayor of Pekanbaru period 2001-2011 for his acquisition of voice in first round of Riau gubernatorial election at Pekanbaru in 2013.The results showed a positive relationship between leadership and acquisition of voice. Positive and significant correlation indicates that more satisfy people of leadership make greater effect on acquisition of voice. The majority of survey respondents (48.5%) agreed with Herman Abdullah leadership as Mayor of Pekanbaru in 2001-2011. This proves the Herman Abdullah leadership had an effect on his acquisition of voice In First Round of Riau gubernatorial election at Pekanbaru In 2013.Keyword: Leadership, Acquisition of Voice, first round of Riau gubernatorial election.